Presentation of cerebral and cervical arterial dissections in botucatu, brazil: Case series - Modolo, Gabriel Pinheiro [UNESP]; Fujisao, Elaine Keiko [UNESP]; Padula, Niura Aparecida de Moura Ribeiro; da Silva, Felipe Aranibar Soares [UNESP]; Luvizutto, Gustavo José [UNESP]; Sobreira, Marcone Lima [UNESP]; Bazan, Rodrigo; de Freitas, Carlos Clayton Macedo [UNESP] (FapUNIFESP (SciELO), 2021)
Spontaneous dissection of the cervical and cerebral arteries is an important cause of stroke and disability in young patients. In this report, the authors present a case series of patients with spontaneous carotid, vertebral, or cerebral artery dissection who underwent digital angiography. A review of the published literature on this subject is also presented.
Apresentação de dissecções arteriais cerebrais e cervicais em botucatu, brasil: Uma série de casos
Keywords: Artery dissection; Endovascular treatment; Stroke